PELITA: Peningkatan Literasi Anak melalui Pendekatan Participatory Learning and Ecosystem Development di Desa Cimanggu II, Bogor - Ilmiawati, Auliya; Nazhifah, Athiq; Wulandari, Desi; Sagraha, Ghiffari Kenang; Nasution, Lise Meitner Aribah; Rahmah, Lutfita Anisa; Fiqri, Muhammad; Asyari, R. Mugni Chairil Arbi; Larasati, Rizki Marsha; Kenang Sagraha, Ghiffari (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Cimanggu II Village, located in Cibungbulang Subdistrict, Bogor Regency, has several libraries. However, libraries and literacy interest in this village are still relatively low, as evidenced by poorly maintained facilities and low public understanding of literacy issues. The Pelita (Improving Children's Literacy through Participatory Learning and Ecosystem Development) program was implemented in Cimanggu II Village to address the low interest in reading due to the poor condition of the Lentera Community Reading Park (TBM) and the minimal community support. The objectives of this activity include improving children's literacy skills, revitalizing the Lentera Community Library, strengthening community and external stakeholder involvement, and creating an inclusive literacy environment. This program integrates Community Engagement, Enriched Learning Environment, and Fun Learning Method based on Maslow's Hierarchy of Needs theory. The Pelita Sehati subprogram focuses on revitalizing TBM facilities and digitizing data, while Pelita Cerdas emphasizes improving literacy through interactive activities such as storytelling, magic chemistry, reading aloud, book reviews, story writing, and reading-based creative projects. The results showed a significant increase in children's interest in reading, literacy skills, courage, creativity, and participation. Evaluation using the Logic Model confirms the relationship between inputs, activities, outputs, and outcomes, while the sustainability strategy using the Quadruple Helix Model strengthens multi-stakeholder collaboration. This program has succeeded in building an inclusive, sustainable, and impactful literacy ecosystem.